A chain-interactive innovation model for the learning economy: Prelude for a proposal - Caraça, João (2007)
The implementation of innovation has a central role in the dynamic knowledge economy of the twenty-first century. The ability to assemble new expertise and commercialise new business propositions constitutes one of the central characteristics in today's globalising, learning-intensive, fast changing economic life. This paper sets out to articulate a stylised understanding of the modern innovation process on the basis of the currently available understanding in the innovation studies tradition. The conceptual model seeks to capture the essential features of organisations engaged in developing dynamic factors of competitiveness.